Reducing Burn‐In Loss of Organic Photovoltaics by a Robust Electron‐Transporting Layer. Issue 12 (1st May 2019) - Oh, Hyerim; Sim, Ha‐Bin; Han, Seung Hee; Kwon, Yong‐Ju; Park, Jae Hyun; Kim, Myung Hwa; Kim, Jin Young; Kim, Won‐Suk; Kim, Kyungkon
Abstract: It is revealed that instability of interface between photoactive layer and electron‐transporting layer (ETL) is one of the causes of the rapid degradation of organic photovoltaics (OPV) performance during initial operation (burn‐in loss) under the light soaking. The stability of OPV is greatly enhanced by applying a robust ETL composed of TiO2 nanoparticles (TNPs). The TNPs bound with π–π interactive 3‐phenylpentane‐2, 4‐dione (TNP–Ph) form more robust ETLs than those bound with van der Waals interactive 3‐methyl‐2, 4‐pentanedione TNP (TNP–Me). The OPV with TNP–Ph maintains 73% of its initial power conversion efficiency (PCE) after 1000 h of light soaking, whereas the PCE of OPV with TNP–Me substantially reduces to 25% of initial PCE. The impedance analysis reveals that the burn‐in loss is due to increase of resistance at the TNP ETL/photoactive layer interface during the light soaking. The transmission electron microscopy analysis shows that the TNP–Ph maintains most clear and robust interface with photoactive layer after the light‐soaking test. This is attributed to the strong π–π interaction between phenyl rings of TNP–Ph. However, the TNP–Me bound with van der Waals interactive organic ligands penetrates the photoactive layer during the light‐soaking test. Abstract : Stability of organic solar cell is enhanced by utilizing robust electron‐transporting layer composed of TiO2 nanoparticle chelated with phenyl acetylacetone.